Structure-Based Design of Potential anti-Dengue Compounds against the Envelope Glycoprotein of Dengue 2 Virus - Hanson. G,; Asmah. N.E.; Adzagbo. M.A.; et al. (J. Comput. Biophys. Chem, 2025)
The spread of dengue fever has resulted in several deaths for which no drug is currently efficacious. A potential target for the development of an antiviral drug that prevents conformational changes and interferes with mem brane fusion is the Dengue β-OG binding pocket. This study aimed to identify potential natural product leads with the propensity to inhibit the envelope protein. Three known inhibitors (DV2419-447, NITD449 and Doxycycline) and 43,465 compounds compiled from naturally derived product libraries comprising AfroDb, NANPDB and TCMID were screened against the envelope protein’s energy-minimized structure as an integrated library. After the molecular docking studies involving 7200 prefiltered compounds and three known inhibitors using AutoDock Vina, 620 top-identified hits were physiochemically and pharmacologically profiled using SwissADME. Compared with reported potent inhibitors, the lead compounds were shown to have better binding affinities greater than −8.6kcal/mol. Four predicted lead com pounds comprising ZINC000014721518, ZINC000005195832, ZINC000014819293 and ZINC000004102396 were iden tified to interact with Thr48, Leu198 and Gln49, which are critical residues in the inhibition of membrane fusion. All the potential leads were predicted to be antiviral and membrane permeability inhibitors with Pa>0.300 and Pa>0.500, respectively. ZINC000014756860, ZINC000014819293 and ZINC000003871358 were predicted to be viral entry inhibi tors. Structurally similar compounds have been shown to inhibit Dengue virus (DENV) replication. In-depth molecular dynamics simulations, including MM/PBSA computations, further substantiated the protein–ligand complexes’ stability and favorable binding mechanisms with residues Leu198, Ile270, Thr48 and Phe193. Further experimental evaluation is needed to understand their role in inhibiting DENV viral entry
Research Article
Keywords: Drug discovery; envelope protein; virtual screening